A U-shaped kinetic energy harvester for application in a near-zero energy parking system. (June 2022) - Li, Ning; Jia, Changyuan; Fang, Zheng; Jiang, Zhuojun; Ahmed, Ammar; Hao, Daning; Zhang, Zutao; Luo, Dabing
Highlights: A speed bump-based energy harvesting system is proposed for a parking lot access control system. A U-shaped rack-pinion and ball screw hybrid mechanism are utilized for motion conversion. The converted energy is stored in supercapacitors to power electronic components in the parking lot. The maximum mechanical efficiency was 68.41%, and the average output power was 15.67 W. Abstract: In the urbanization process, the quantity of parking lots is multiplying with a vast potential to generate electricity. This paper proposes a novel speed bump-based energy-harvesting system to capture the wasted kinetic energy of the vehicles passing through the speed bump and produces electrical power. The kinetic energy harvesting (KEH) system is divided into the following four modules: speed bump module, energy transmission module, generator module, and energy storage module. The speed bump module captures the vibration energy generated by the contact between the vehicle and the speed bump. The energy transmission module converts the up-and-down reciprocating motion of the speed bump into the unidirectional rotational motion of the generator shaft through rack-pinion and screw nut-lead screw structures. The generator module converts the rotational mechanical energy into electrical energy, then stored by the supercapacitor in the energy storage module. The MTS bench test showed that the average output power could reach 15.67 W, and the efficiency could reach 68.41%. The results demonstrate that the proposed KEH system can be used as an emergency and backup power source for loop detector sensors, OLED display, video camera, and small electrical equipment for developing a near-zero-energy parking lot access control system.